Financing and its effect on the liquidity of commercial micro-enterprises in Quevedo (REDEL. Revista Granmense de Desarrollo Local, 2025)
Financing is a key element to ensure the liquidity of micro-enterprises, especially in sectors where access to economic resources is limited. The objective of this article is to analyze the relationship between financing and the liquidity of micro-enterprises in the commercial sector of Quevedo. The research was developed using a quantitative approach with a non-experimental, cross-sectional design, applying surveys to a sample of 294 micro-enterprises selected through simple random sampling. Data were processed using descriptive and correlational statistics with SPSS v.26. The results show that financing from banks and cooperatives improves liquidity levels, while informal financing is associated with higher financial risks. The correlational analysis revealed a positive and significant relationship between access to financing and liquidity. It was concluded that formal financing constitutes a strategic tool for strengthening the payment capacity of micro-enterprises and ensuring their sustainability, although access to it remains limited.
Keywords: financing; liquidity; microenterprises; commercial sector; financial inclusion